Investigating the Effectiveness of Online Learning in ELT: EFL Learners’ Perception: English - Iman, Jaya Nur (Journal of English Development, 2025)
Learning English online seems to be challenging for lecturers in English language instruction. This inquiry was about to investigate EFL learners’ perception on the effectiveness of online learning in English language teaching viewed from psychological and linguistic standpoint.  A quantitative research design was used which primarily concerned on descriptive statistics of the EFL learners’ perception due to the integration of online learning in English language teaching. Twenty-one university students from non-English major were selected purposively. A set of well-designed questionnaire items with the format of close-ended was utilized. The research findings found out that positive perceptions were owned by the EFL learners in terms of psychological standpoints particularly on happiness, motivation, convenience, boredom, anxiety, learning independence, learning focus, excluding enthusiasm. In addition, positive perceptions were owned by the EFL learners in relation to linguistic standpoints particularly on listening skill, speaking skill, reading skill, writing skill, grammar understanding, and content knowledge after learning English online in English language teaching. Some pedagogical implications were noted for English lecturer, future participants, concerned stakeholder, and other educational researchers.